Noncardiac malformations in congenital heart disease: a retrospective analysis of 305 pediatric autopsies - Güçer, Safak; Ince, Tolga; Kale, Gülsev; Akçören, Zuhal; Ozkutlu, Süheyla; Talim, Beril; Cağlar, Melda (The Turkish Journal of Pediatrics, 2005)
Congenital heart disease (CHD) is one of the important groups of birth defects and contributes significantly to infant mortality. Extracardiac anomalies occur in 15-45% of cases with CHD. In this retrospective study, autopsies of cases born alive and diagnosed as CHD between 1977-2002 at Hacettepe University Ihsan Doğramaci Children's Hospital, Pediatric Pathology Department, were investigated. In this period, a total of 3320 autopsies were performed and the incidence of CHD was 9.1%. The most commonly encountered CHD was ventricular septal defect (VSD) (15.3%). In 45.9% of cases, one or more extracardiac malformations were present. The most commonly encountered extracardiac malformation was craniofacial malformations. Less commonly seen were malformations of genitourinary, musculoskeletal, respiratory, gastrointestinal, central nervous systems and spleen anomalies. Ventricular septal defect, atrial septal defect (ASD), aortic coarctation, single ventricle, pulmonary stenosis, hypoplastic right heart syndrome, double outlet right ventricle, ASD+VSD, aortic arcus anomalies, and right and left atrial isomerism cases were often (>50%) accompanied by extracardiac malformations. No extracardiac malformations were detected accompanying pulmonary atresia with intact interventricular septum, Ebstein malformation, and mitral stenosis (MS). Spleen malformation was significantly high in cases with single ventricle (p